Simulated Winter Incubation of Soil With Swine Manure Differentially Affects Multiple Antimicrobial Resistance Elements - Miller, Daniel N.; Jurgens, Madison E.; Durso, Lisa M.; Schmidt, Amy M. (Frontiers in Microbiology, 2020)
Gastrointestinal bacteria that harbor antibiotic resistance genes (ARG) become enriched with antibiotic use. Livestock manure application to cropland for soil fertility presents a concern that ARG and bacteria may proliferate and be transported in the environment. In the United States, manure applications typically occur during autumn with slow mineralization until spring planting season. A laboratory soil incubation study was conducted mimicking autumn swine manure application to soils with concentrations of selected ARG monitored during simulated 120-day winter incubation with multiple freeze-thaw events. Additionally, the effects of two soil moistures (10% and 30% water holding capacity) and two manure treatments [raw versus hydrated lime alkaline stabilization (HLAS)] were assessed. Fourteen tetracycline resistance genes were evaluated; tet(D), tet(G), and tet(L) were detected in background soil while swine manure contained tet(A), tet(B), tet(C), tet(G), tet(M), tet(O), tet(Q), and tet(X). By day 120, the manure-borne tet(M )and tet(O) were still detected while tet(C), tet(D), tet(L), and tet(X) genes were detected less frequently. Other tet resistance genes were detected rarely, if at all. The sum of unique tet resistance genes among all treatments decreased during the incubation from an average of 8.9 to 3.8. Four resistance elements [intI1, blactx-m-32, sul(I), erm(B)] and 16s rRNA genes were measured using quantitative PCR. ARG abundances relative to 16S abundance were initially greater in the raw manure compared to background soil (-1.53 to -3.92 log abundance in manure; -4.02 to <-6.7 log abundance in soil). In the mixed manure/soil, relative abundance of the four resistance elements decreased (0.87 to 1.94 log abundance) during the incubation largely because 16S rRNA genes increased by 1.21 log abundance. Throughout the incubation, the abundance of intI1, blactx-m-32, sul(I), and erm(B) per gram in soil amended with HLAS-treated manure was lower than in soil amended with raw manure. Under low initial soil moisture conditions, HLAS treatment reduced the abundance of intI1 and resulted in loss of blactx-m-32, sul(I), and erm(B)] compared to other treatment-moisture combinations. Although one might expect antibiotic resistance to be relatively unchanged after simulated winter manure application to soil, a variety of changes in diversity and relative abundance can be expected.